2023
DOI: 10.3390/healthcare11020243
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Non-Alcoholic Fatty Liver Disease and Dynapenia in Men Diagnosed with Type 2 Diabetes Mellitus

Abstract: Background: Dynapenia and non-alcoholic fatty liver disease (NAFLD) are common, especially in the middle and advanced-age diabetic male population. We aimed to examine the clinical features, NAFLD severity, and parameters associated with the presence of dynapenia in type 2 diabetes mellitus (T2DM) cases. Material and Methods: One hundred thirty-five male patients diagnosed with T2DM between 45 and 65 years of age were included. Patients were staged by ultrasonography according to NAFLD status. Results: There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Insulin can accelerate protein synthesis, and its breakdown can The loss of muscle mass reduces exercise tolerance, which can result in obesity (particularly the buildup of visceral fat), 17 and increase the risk of NAFLD. 18 By altering the metabolism of fat muscles and IR, loss of muscle mass and obesity primarily encourage lipotoxic effects and have a negative impact on NAFLD onset and progression. 19 Sarcopenia and obesity increase the risk of NAFLD 20 and all-cause mortality compared to obesity alone.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin can accelerate protein synthesis, and its breakdown can The loss of muscle mass reduces exercise tolerance, which can result in obesity (particularly the buildup of visceral fat), 17 and increase the risk of NAFLD. 18 By altering the metabolism of fat muscles and IR, loss of muscle mass and obesity primarily encourage lipotoxic effects and have a negative impact on NAFLD onset and progression. 19 Sarcopenia and obesity increase the risk of NAFLD 20 and all-cause mortality compared to obesity alone.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no prior studies have examined the association between muscle strength and the risk of MAFLD. However, few studies have examined the association between muscle strength and NAFLD[ 31 ]. One cross-sectional study, utilizing data from the KNHANES database, found an association between low muscle strength and NAFLD[ 8 ].…”
Section: Discussionmentioning
confidence: 99%